APLIKASI LIMBAH CAIR PABRIK KELAPA SAWIT DAN ZEOLIT TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) - Frengki H Napitupulu; Edison Anom; M.Amrul Khoiri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Plant oil palm (Elaeis guineensis Jacq.) is one of commodity plantation in Riau as a source of vegetable oil. In order to increase the production of the necessary good breeding. Seedling growth is strongly influenced by the availability of nutrients, so it takes fertilization. Fertilizers used are Palm Oil Mill Effluent (LCPKS). LCPKS contains nutrients that can be absorbed by plants. LCPKS has the disadvantage that volatile, so it need a way to overcome that problem. One solution that is used is the granting of Zeolite. Zeolite is able to bind nutrients that are available in a long time for plants. This research aims to get the best treatment on the growth of oil palm seedlings. Research conducted at the experimental field of the Faculty of Agriculture, University of Riau. This research has been going on for three months starting from February to April 2015. The research was conducted using a completely randomized design (CRD) factorial. The first factor is the Palm Oil Mill Effluent with 3 levels consisting of 0 ml, 195 ml and 390 ml. The second factor is a Zeolite with 3 levels consisting of 0 g, 50 g and 100 g. The combination is repeated 4 times so that there are 36 units of trial and each experimental unit consisted of two plants, so the total is 72 plants. Parameters measured were seedling high accretion (cm), number of leaves (pieces), stem diameter (cm), root volume (ml), the ratio of crown roots, and seedling dry weight (g). Statistical analysis using ANOVA followed by Duncan's Multiple Range Test at 5%. The results showed that there was no interaction LCPKS and Zeolite on all parameters of observation. Combination of LCPKS 390 ml and 50 g zeolites tend to produce the best growth on the parameters in the number of leaves, stem diameter and root volume. Keywords: Palm Oil Mill Effluent, Zeolit and Oil Palm